Single‐nucleotide polymorphisms in the LRWD1 gene may be a genetic risk factor for Japanese patients with Sertoli cell‐only syndrome. (28th February 2013) - Miyamoto, T.; Koh, E.; Tsujimura, A.; Miyagawa, Y.; Saijo, Y.; Namiki, M.; Sengoku, K.
Summary Genetic mechanisms have been implicated as a cause of some cases of male infertility. Recently, ten novel genes involved in human spermatogenesis, including human LRWD1, have been identified by expression microarray analysis of human testictissue. The human LRWD1 protein mediates the origin recognition complex in chromatin, which is critical for the initiation of pre‐replication complex assembly in G1 and chromatin organization in post‐G1 cells. The Lrwd1 gene expression is specific to the testis in mice. Therefore, we hypothesized that mutation or polymorphisms of LRWD1 participate in male infertility, especially azoospermia. To investigate whether LRWD1 gene defects are associated with azoospermia caused by SCOS and meiotic arrest (MA), mutational analysis was performed in 100 and 30 Japanese patients by direct sequencing of the coding regions, respectively. Statistical analysis was performed for patients with SCOS and MA and in 100 healthy control men. No mutations were found in LRWD1; however, three coding single‐nucleotide polymorphisms (SNP1‐SNP3) could be detected in the patients. The genotype and allele frequencies in SNP1 and SNP2 were notably higher in the SCOS group than in the control group (P < 0.05). These results suggest the critical role of LRWD1 in human spermatogenesis.